One-Stage Arthroscopic Reduction Combined with Multiligament Reconstruction or Repair for Irreducible Posterolateral Knee Dislocation: A Retrospective Case Series with Minimum 2-Year Follow-Up - Hongwu, Zhuo; Li, Jian (The Journal of Knee Surgery, 2018)
The purpose of this study was to evaluate the clinical outcomes after arthroscopic management of irreducible posterolateral knee dislocation. Twenty-one patients with irreducible posterolateral knee dislocation were treated in our institution from January 2009 to May 2014. Inclusion criteria were as follows: (1) patients who underwent one-stage arthroscopic reduction combined with multiligament reconstruction or repair and (2) patients with a minimum 2-year follow-up. Knee stability was assessed using physical examination and side-to-side differences (SSD) determined with a KT-1000 arthrometer and Telos stress device. Other assessments included the International Knee Documentation Committee (IKDC) subjective score, Lysholm score, Tegner score, and patient satisfaction rate. Thirteen of the 21 patients (8 males and 5 females) met our inclusion criteria and were included in this analysis. The mean age was 37.8 years (range, 27–56 years). The mean time from injury to surgery was 1.84 days (range, 1–3 days). The mean follow-up period was 32.6 months (range, 24–46 months). At the final follow-up, with the exception of one patient who had an abnormal valgus stress test, all patients achieved normal or nearly normal Lachman test, pivot shift test, posterior drawer test, and varus and valgus stress tests. The mean SSD of total anterior–posterior translation and isolated anterior translation determined with a KT-1000 arthrometer were 2.15 ± 1.57 mm (range, 0–6 mm) and 1.61 ± 0.86 mm (range, 1–4 mm), respectively. The mean SSD of anterior translation, posterior translation, and medial and lateral joint gapping determined with a Telos stress device were 2.23 ± 0.92 mm (range, 1–4 mm), 3.23 ± 1.16 mm (range, 2–5 mm), 1.77 ± 1.87 mm (range, 0–7 mm), and 0.46 ± 0.52 mm (range, 0–2 mm), respectively. The IKDC subjective score, Lysholm score, and Tegner score improved significantly postoperatively (p = 0.001) with a satisfaction rate of 84.6%. One-stage arthroscopic reduction combined with multiligament reconstruction or repair was an effective, reliable treatment for irreducible posterolateral knee dislocation. This is a case series with level of evidence as IV.
Keywords: knee; dislocation; ligament; reconstruction